PENGARUH EASE OF USE DAN TRUST TERHADAP REPURCHASE INTENTION YANG DIMEDIASI OLEH E-SATISFACTION PADA PENGGUNA APLIKASI BELANJA ONLINE SHOPEE DI ACEH - Syarifah Diansari; Halimatussakdiah Halimatussakdiah (Departemen Manajemen, 2021)
The purpose of this study is to find out the effect of Ease of Use and Trust towards Repurchase Intention mediated by E-Satisfaction. The society of Aceh Province who had done the purchase on Shopee application for at least twice were used as population. The sample in this study consisted of 300 samples. The sampling technique used Non Probability Sampling and the type of sampling was Purposive Sampling. Data collected in this study were using questionnaire. The Structural Equation Modeling (SEM) was used on analytical method to determine the effect of variables involved. The result shows that ease of use has a significant effect on e-satisfaction, trust has a significant effect on e-satisfaction, ease of use has no significant effect on repurchase intention, trust has a significant effect on repurchase intention, e-satisfaction has a significant effect on repurchase intention, e-satisfaction mediates the effect of ease of use on repurchase intention, and e-satisfaction mediates the effect of trust on repurchase intention.